2015
DOI: 10.5897/jmpr2015.5902
|View full text |Cite
|
Sign up to set email alerts
|

Phytoconstituents, antimicrobial and antioxidant properties of the leaves of Persea americana Mill cultivated in Ghana

Abstract: The leaves of Persea americana are widely used for ethno-medicinal purposes worldwide. This study assessed the antimicrobial and antioxidant activities of the methanol, ethyl acetate, chloroform and petroleum ether leaves extracts of P. americana. Extracts displayed variable antimicrobial activities that were microorganism-specific. The methanolic extract displayed the most potent antimicrobial activities with the largest zones of inhibition (0-1.8 mm) in the agar diffusion assay and with the lowest minimum in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…All plants tested in the present study ( Table 1 ) are used traditionally to treat several affections or diseases with symptoms related to microbial infections [ 8 – 10 , 16 , 17 , 19 , 20 , 27 , 29 , 40 ], and data obtained therefore consolidate their traditional use. The presence of previously reported secondary metabolites in the tested plants [ 11 , 12 , 18 , 21 , 22 , 27 , 30 , 31 , 40 , 41 ] ( Table 1 ) is also in accordance with the present studies and could in part justify their antibacterial effects. Natural compounds belonging to terpenoids (for example, camosic acid and isopimarane derivatives), flavonoids (for example, 5′-methoxyhydnocarpin) as well as alkaloids (for example, pheophorbide A or reserpine) and others have been identified as efflux pumps inhibitors [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…All plants tested in the present study ( Table 1 ) are used traditionally to treat several affections or diseases with symptoms related to microbial infections [ 8 – 10 , 16 , 17 , 19 , 20 , 27 , 29 , 40 ], and data obtained therefore consolidate their traditional use. The presence of previously reported secondary metabolites in the tested plants [ 11 , 12 , 18 , 21 , 22 , 27 , 30 , 31 , 40 , 41 ] ( Table 1 ) is also in accordance with the present studies and could in part justify their antibacterial effects. Natural compounds belonging to terpenoids (for example, camosic acid and isopimarane derivatives), flavonoids (for example, 5′-methoxyhydnocarpin) as well as alkaloids (for example, pheophorbide A or reserpine) and others have been identified as efflux pumps inhibitors [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 92%
“…The leaves of P. americana are widely used for ethnomedicinal purposes worldwide. In order to confirm its multiple medicinal properties, a study conducted by Nathaniel et al [ 18 ] showed that the methanolic extract from leaves of P. americana had good antimicrobial activity against enteric microorganisms (Gram-negative and Gram-positive bacteria and also yeasts). This is in accordance with the present study as we also found that methanol extracts of both leaves and bark of the plant exhibited similar activities against several MDR bacteria, with leaves' extract having good inhibitor effects (64 μ g/mL) against the E. coli AG102 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Ilozue et al 14 identificaron en la semilla de Persea americana, esteroides, alcaloides, saponinas, taninos, flavonoides y glucósidos cardiacos. Owusu et al 15 determinaron que el extracto metanólico de las hojas de Persea americana Mill. muestra actividad antimicrobiana potente con las mayores zonas de inhibición (0 -1,8 mm) en el ensayo de difusión en agar y con la más baja CMI en el ensayo de dilución en caldo contra un panel de microorganismos que incluye Bacillus subtilis, Escherichia coli, Salmonella typhi, Streptococcus aureus, Pseudomonas aeruginosa y Candida albicans; datos similares al obtenido apoyan el uso etnomedicinal de las hojas de Persea americana para el tratamiento de las infecciones.…”
Section: Resultados Y Discusiónunclassified
“…In this sense, recently, it has been shown that the extract from P. americana epicarp has an antioxidant capacity and can be used as a functional food ingredient or nutraceuticals with antioxidant and anti-aging activity [11]. In the same line of evidence, some reports have demonstrated that the extract from Persea americana leaves has antibacterial, antifungal, and antioxidant properties [12][13][14].…”
Section: Introductionmentioning
confidence: 93%
“…The extract obtained from its leaves contains tannins, anthocyanins, flavonoids, kaempferol, alkaloids, triterpenoids, carbohydrates, and fatty acids [12,15,[24][25][26], and these compounds are synthesized by secondary metabolism and usually possess complex structures [27]. On this basis, it is clear that leaves from P. americana represent a potential source of molecules with antibacterial effects.…”
Section: Introductionmentioning
confidence: 99%